Color coded perfusion imaging with contrast enhanced ultrasound (CEUS) for post-interventional success control following trans-arterial chemoembolization (TACE) of hepatocellular carcinoma. - Janine Rennert; Isabel Wiesinger; Andreas Schicho; Lukas Philip Beyer; Philipp Wiggermann; Christian Stroszczynski; Ernst Michael Jung (PLoS ONE, 2019)
Aim Evaluation of an external color coded perfusion quantification software with CEUS for the post-interventional success control following TACE in patients with HCC. Material and methods 31 patients (5 females, 26 males, age range 34-82 years, mean 66.8 years) with 59 HCC lesions underwent superselective TACE using DSM Beads between 01/2015 and 06/2018. All patients underwent CEUS by an experienced examiner using a convex multifrequency probe (1-6 MHz) within 24 hours following TACE to detect residual tumor tissue. Retrospective evaluation using a perfusion quantification software regarding pE, TTP, mTT, Ri and WiAUC in the center of the lesion, the margin and surrounding liver. Results In all lesions, a post-interventional visual reduction of the tumor microvascularization was observed. Significant differences between center of the lesion vs. margin and surrounding liver were found regarding peak enhancement (867.8 ± 2416 center vs 2028 ± 3954 margin p<0.005) and center 867.8 ± 2416 vs 2824 ± 4290 surrounding liver, p<0.0001)). However, no significant differences were found concerning Ri, WiAuC, mTT and TTP. Conclusion CEUS with color- coded perfusion imaging is a valuable supporting tool for post-interventional success control following TACE of liver lesions. Peak enhancement seems to be the most valuable parameter.